Nontuberculous mycobacteria in respiratory tract infections, eastern Asia - Simons, Sami; van Ingen, Jakko; Hsueh, Po-Ren; Van Hung, Nguyen; Dekhuijzen, P N Richard; Boeree, Martin J; van Soolingen, Dick (Emerging infectious diseases, 2011)
To characterize the distribution of nontuberculous mycobacteria (NTM) species isolated from pulmonary samples from persons in Asia and their association with pulmonary infections, we reviewed the literature. Mycobacterium avium complex bacteria were most frequently isolated (13%-81%) and were the most common cause of pulmonary NTM disease (43%-81%). Also pathogenic were rapidly growing mycobacteria (M. chelonae, M. fortuitum, M. abscessus). Among all NTM isolated from pulmonary samples, 31% (582/1,744) were considered clinically relevant according to American Thoracic Society diagnostic criteria. Most patients were male (79%) and had a history of tuberculosis (37%). In Asia, high prevalence of rapidly growing mycobacteria and a history of tuberculosis are distinct characteristics of pulmonary NTM disease. This geographic variation is not well reflected in the American Thoracic Society criteria for NTM infections and could be incorporated in future guidelines.